Diversidade de afídeos na cultura do algodoeiro no município de Campo Verde (MT) - Michelotto, Marcos Doniseti [UNESP]; Busoli, Antonio Carlos [UNESP] (My University, 2003)
This work was carried out in Campo Verde, Mato Grosso State, Brasil, and its objective was to determine the occurrence of aphid species (Hemiptera: Aphididae) on cotton field (Gossypium hirsutum L.). The aphids were sampled both directly on plants and with Moericke's traps. The samplings were accomplished every other day during 60 days. Aphis gossypil Glover prevailed on cotton plants. Winged forms accidental as Aphis spiraecola Patch and Rhopalosiphum padi (Linnaeus) also occurred. In the water-pan traps 2280 winged aphids were trapped, which are from 13 species: R. padi (52.6% of total), A. spiraecola (26.4%), A. gossypii (8.9%), Rhopalosiphum maidis (Fitch) (5.3%), Geopemphigus floccosus (Moreira) (3.1%), Uroleucon ambrosiae (Thomas) (1.5%), Rhopalosiphum rufiabdominalis (Sasaki) (1.3%), Myzus persicae (Sulzer) (0.4%), Sipha flava (Forbes) (0.3%), Pentalonia nigronervosa Coquerel (0.1%), Tetraneura nigriabdominalis (Sasaki) (0.1%), Lizerius melanocallis (Quednau) (0.1%) and Toxoptera citricidus (Kirkaldy) (0.1%). In the direct samplings on cotton plants were present both wingless and winged forms of the A. gossypii and winged forms of the A. spiraecola and R. padi. In the Moericke's traps, the main captured species are R. padi, A. spiraecola, A. gossypii and R. maidis.
Aphids diversity on cotton field in Campo Verde, Mato Grosso State
Keywords: Aphid/host relation; Aphididae; Gossypium; Sampling; Yello trap